Correction: Freezing temperature controlled deep eutectic solvent dispersive liquid–liquid microextraction based on solidification of floating organic droplets for rapid determination of benzoylureas residual in water samples with assistance of metallic salt. Issue 8 (24th January 2018) - Yang, Miyi; Hong, Kun; Li, Xiaoqiang; Ge, Fangji; Tan, Yuqing
Abstract : Correction for 'Freezing temperature controlled deep eutectic solvent dispersive liquid–liquid microextraction based on solidification of floating organic droplets for rapid determination of benzoylureas residual in water samples with assistance of metallic salt' by Miyi Yang et al., RSC Adv., 2017, 7, 56528–56536.